Exploring the role of green brand positioning in determining green product purchase intention - Krissanya, Nofriska; Sholikhah, Sholikhah; Berutu, Meta Bara; Sari, Dewi Agustin Pratama (International Journal of Applied Economics, Finance and Accounting, 2023)
In this study, we investigate the relationship between green brand positioning (GBK), attitude toward green brand (AGB) and green brand knowledge (GBK) on green product, specifically in beauty and body care products. It also sought to examine consumer’s purchase intention (PI) of this product using those variables. The methodology which is used to analyse the data obtained is using an exploratory quantitative approach. The data evaluated by Partial Least Square – Structural Equation Model (PLS-SEM). This study used purposive sampling techniques to determine the sample of employees who work in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek), Indonesia. The outcomes indicate that all these factors contribute to purchase intention of this green beauty and body care product. This study is also found that GBP has a positive direct contribution to AGB, GBK, and PI. Originality and practical implications from this study are that, the green product companies must pay attention to the brand positioning because it would alter consumer’s attitude and intention towards of green products. Thus, companies should focus more on developing promotional messages that are more directed towards sustainable values or optimizing communities that support sustainability lifestyles. More deeply, eco-friendly beauty and body care products are very widely used today, so the results of this research are expected to contribute in terms of how can customer’s intensions are increased in buying these products.